DEVELOPMENT AND STANDARDIZATION OF A LIFE SKILLS ASSESSMENT SCALE (LSAS-21) - Naqvi, Shumila Fatma; Chandra, Ritu (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The present study focuses on the development and standardization of a Life Skills Assessment Scale (LSAS-21) designed to measure essential psychosocial competencies required for effective functioning in daily life. Life skills such as self-awareness, communication, resilience, empathy, participation, critical thinking, creativity and problem-solving, decision-making, and negotiation play a crucial role in personal, social, and academic adjustment. The initial item pool was developed after an extensive review of literature and existing life skills frameworks. The scale was prepared using a Likert-type format and evaluated by subject experts for content validity. A pilot study was conducted on a sample of N = 30, and the reliability was found to be high (α = 0.953). Principal Component Analysis (PCA) indicated a multidimensional structure of the scale. The main standardization study was conducted on a sample of N = 400, and the reliability of the final scale was α = 0.702. Construct validity was examined using correlation analysis and factor analysis. Pearson’s correlation showed positive and significant relationships among items, indicating a common underlying construct. Further, Principal Component Analysis with Varimax rotation supported the suitability of the data for factor analysis. The KMO value was 0.755, and Bartlett’s Test of Sphericity was significant (χ² = 837.690, df = 210, p < .001), confirming adequacy for factor analysis. The final LSAS-21 consists of 21 items covering nine dimensions: Self-Awareness, Communication, Resilience, Empathy, Participation, Critical Thinking, Creativity and Problem Solving, Decision Making, and Negotiation. The scale demonstrates satisfactory psychometric properties and can be effectively used by researchers, counselors, and educators for assessing life skills.